Beyond Humanism: Reflections on Trans- and Posthumanism - Sorgner, Stefan; Ticchione Sáez, Diego; Alarcón Acuña, Hugo (Revista Ethika+, 2022)
I am focusing here on the main counterarguments that were raised against a thesis I put forward in my article “Nietzsche, the Overhuman, and Transhumanism” (2009a), namely that significant similarities can be found on a fundamental level between the concept of the posthuman, as put forward by some transhumanists, and Nietzsche’s concept of the overhuman. The articles with the counterarguments were published in the recent “Nietzsche and European Posthumanisms” issue of The Journal of Evolution and Technology (January-July 2010). As several commentators referred to identical issues, I decided that it would be appropriate not to respond to each of the articles individually, but to focus on the central arguments and to deal with the counterarguments mentioned in the various replies. I am concerned with each topic in a separate section. The sections are entitled as follows: 1. Technology and evolution; 2. Overcoming nihilism; 3. Politics and liberalism; 4. Utilitarianism or virtue ethics?; 5. The good Life; 6. Creativity and the will to power; 7. Immortality and longevity; 8. Logocentrism; 9. The Third Reich. When dealing with the various topics, I am not merely responding to counterarguments; I also raise questions concerning transhumanism and put forward my own views concerning some of the questions I am dealing with.